2020
DOI: 10.1080/00036846.2020.1734184
|View full text |Cite
|
Sign up to set email alerts
|

Financial crises, debt overhang, and firm growth in transition economies

Abstract: We examine the effects of the global financial crisis of 2008 and the European debt crisis of 2011 on the relationship between capital structure, investments, and performance for Eastern European companies. While the existing literature documents how firms' investments are sensitive to the availability of internal funds and to debt holdings, we further investigate whether this investment sensitivity also translates in different levels of performance, and document that capital structure indeed has both a direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Furthermore, the consistency in operating performance also reduces the need of holding short-term liquid assets for cash flow management, thus allowing the firm to use these spare resources in value-adding operations and strategic investments. Finally, CRM provides a natural shield against debt overhang (Botta, 2020).…”
Section: Corporate Risk Management and Firm Performancementioning
confidence: 99%
“…Furthermore, the consistency in operating performance also reduces the need of holding short-term liquid assets for cash flow management, thus allowing the firm to use these spare resources in value-adding operations and strategic investments. Finally, CRM provides a natural shield against debt overhang (Botta, 2020).…”
Section: Corporate Risk Management and Firm Performancementioning
confidence: 99%
“…Pirtea et al [31] reported a non-linear and negative relation between debt ratio and profitability for the Romanian public firms, which support the pecking order theory. Employing a large sample of public firms from Eastern Europe over the period from 2004-2017, Botta [32] found that a higher-than-optimal level of leverage harms capital expenditure and returns. None of these studies tested the role of fiscal policy on the relationship between leverage and firm growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies with European firm-level micro data such as Kalemli-Özcan, Laeven, and Moreno (2020) and Popov, Barbiero, and Wolski (2018) find conflicting evidence with respect to the investment level and efficiency effects of high debt. Inevitably, post-2008 data are tinted by the financial crisis (Giroud and Mueller, 2017;Kuchler, 2020;Botta, 2020). During this period, investment may have fallen, not due to overhang, but because impaired banks and other intermediaries constricted the supply of credit to preserve capital (Chodorow-Reich, 2014).…”
Section: Introductionmentioning
confidence: 99%